The effectiveness of extracurricular activities organized by UiTM Sarawak/ Nurul Hasanah Hussien - Hussien, Nurul Hasanah (2011)
The purpose ofthe study is to analysis effectiveness of extracurricular activities organized by UiTM Sarawak and to seek out the most appropriate suggestions and recommendations in order to improve the performance of student who participating in extracurricular activities. The level of respondent’s perception, experience and expectation were measured to identify whether extracurricular activities give more advantages than disadvantages. Throughout the period of study, one hundred and twenty-four (124) responses had been received and the data collected was analyzed. According to Phil Avery (2007), Geography Teacher, in his video, he explained that extracurricular activities refer to any activities that facilitate learning outside the classroom. They are not falling within the scope of the regular curriculum because they are scheduled outside of the regular class day. The common purpose or objective of extracurricular activities is to help the students to develop unique talents and skills they posses.